Down-regulation of TUFM impairs host cell interaction and virulence by Paracoccidioides brasiliensis (2019)
ABSTRACT : The genus Paracoccidioides consist of dimorphic fungi geographically limited to the subtropical regions of Latin America, which are responsible for causing deep systemic mycosis in humans. However, the molecular mechanisms by which Paracoccidioides spp. causes the disease remain poorly understood. Paracoccidioides spp. harbor genes that encode proteins involved in host cell interaction and mitochondrial function, which together are required for pathogenicity and mediate virulence. Previously, we identifed TufM (previously known as EF-Tu) in Paracoccidioides brasiliensis (PbTufM) and suggested that it may be involved in the pathogenicity of this fungus. In this study, we examined the efects of downregulating PbTUFM using a silenced strain with a 55% reduction in PbTUFM expression obtained by antisense-RNA (aRNA) technology. Silencing PbTUFM yielded phenotypic diferences, such as altered translation elongation, respiratory defects, increased sensitivity of yeast cells to reactive oxygen stress, survival after macrophage phagocytosis, and reduced interaction with pneumocytes. These results were associated with reduced virulence in Galleria mellonella and murine infection models, emphasizing the importance of PbTufM in the full virulence of P. brasiliensis and its potential as a target for antifungal agents against paracoccidioidomycosis.